2018
DOI: 10.1007/s00268-018-4807-3
|View full text |Cite
|
Sign up to set email alerts
|

Open Inguinal Hernia Repair: A Network Meta‐analysis Comparing Self‐Gripping Mesh, Suture Fixation, and Glue Fixation

Abstract: The most troublesome complications of inguinal hernia repair are recurrent herniation and chronic pain. A multitude of technological products dedicated to abdominal wall surgery, such as self‐gripping mesh (SGM) and glue fixation (GF), were introduced in alternative to suture fixation (SF) in the attempt to lower the postoperative complication rates. We conducted an electronic systematic search using MEDLINE databases that compared postoperative pain and short‐ and long‐term surgical complications after SGM or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 60 publications
1
29
1
Order By: Relevance
“…Eleven of the included reviews summarised the evidence of different mesh fixation techniques in open inguinal hernia repairs, [16,[24][25][26][27][28][29][31][32][33][34]; eight reported mesh fixation in laparoscopic inguinal hernia repairs [14,15,17,18,30,[35][36][37] and one review reported mesh fixation in both open and laparoscopic repairs [38].…”
Section: Study Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of the included reviews summarised the evidence of different mesh fixation techniques in open inguinal hernia repairs, [16,[24][25][26][27][28][29][31][32][33][34]; eight reported mesh fixation in laparoscopic inguinal hernia repairs [14,15,17,18,30,[35][36][37] and one review reported mesh fixation in both open and laparoscopic repairs [38].…”
Section: Study Detailsmentioning
confidence: 99%
“…Five systematic reviews compared self-gripping mesh with suture and found no significant differences in chronic pain between the two fixation techniques. [24,25,27,31,33] Similarly, one review comparing self-gripping mesh with glue [24] and another review comparing mechanical fixation (tack) with suture fixation for open mesh repair [33] reported comparable rates of chronic pain between fixation techniques. However, most of these reviews reported wide confidence intervals (CIs) around the summary estimate of effect, and clinically important effects favouring either technique for mesh fixation cannot be ruled out with certainty (Table 3).…”
Section: Chronic Groin Painmentioning
confidence: 99%
“…There is weak evidence that lightweight, large pore mesh may reduce the incidence of chronic pain and foreign body related discomfort . Another dimension to the complexity of the issue is the use of mesh fixation devices . Complications of fixation such as migration, recurrence and chronic pain have ensured that this also is an area of considerable debate .…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques for mesh fixations have been used including suture, glue or self-gripping mesh for open hernia repair (OHR); metallic tack, absorbable tack, glue, suture, self-gripping mesh or even non-fixation techniques for laparoscopic hernia repair (LHR). Up to date, there have been eight systematic reviews and meta-analyses (SRMAs) on OHR8–15 (ie, glue vs suture (n=5)8 9 11 12 14 and self-gripping mesh vs suture (n=3))10 13 15 and one network meta-analysis (NMA) 16. For LHR, comparisons were tack and glue (n=6),17–22 fixation versus no fixation (n=4)23–25 and one NMA26.…”
Section: Introductionmentioning
confidence: 99%
“…Although evidences were interesting, the overall results were inconclusive, that is, five SRMAs suggested non-superiority in self-gripping mesh among all mesh fixations in OHR,10 13 15 16 27 whereas five SRMAs favoured glue fixation in decreasing postoperative pain 8 9 11 12 14. Among LHR, three SRMAs favoured glue fixation to decrease postoperative pain,17 18 20 three SRMAs favoured no mesh fixation23–25 and one meta-study suggested all mesh fixations were comparable 19.…”
Section: Introductionmentioning
confidence: 99%